2003
DOI: 10.1046/j.1432-1033.2003.03735.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, cDNA cloning and nucleotide sequencing of a cellulase from the yellow‐spotted longicorn beetle, Psacothea hilaris

Abstract: A cellulase (endo-b-1,4-glucanase, EC 3.2.1.4) was purified from the gut of larvae of the yellow-spotted longicorn beetle Psacothea hilaris by acetone precipitation and elution from gels after native PAGE and SDS/PAGE with activity staining. The purified protein formed a single band, and the molecular mass was estimated to be 47 kDa. The purified cellulase degraded carboxymethylcellulose (CMC), insoluble cello-oligosaccharide (average degree of polymerization 34) and soluble cello-oligosaccharides longer than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 31 publications
2
79
0
Order By: Relevance
“…Cellulase (endo-β-1,4-glucanase) activity in Apriona germari (Coleoptera: Cerambycidae) and Anoplophora glabripennis (Coleoptera: Cerambycidae) was optimum at pH 4.4 and 5.2, respectively (Yin et al 2000;Li et al 2008). The studies on the isolation of cellulase from beetles demonstrated that optimum pH for the highest activity of cellulase from the larval gut of Psacothea hilaris against CMC was 5.5 (Sugimura et al 2003). The results showed that CaCl 2 and MgCl 2 increased significantly endo-β-1,4-glucanase activity in R. ferrugineus.…”
Section: +mentioning
confidence: 99%
“…Cellulase (endo-β-1,4-glucanase) activity in Apriona germari (Coleoptera: Cerambycidae) and Anoplophora glabripennis (Coleoptera: Cerambycidae) was optimum at pH 4.4 and 5.2, respectively (Yin et al 2000;Li et al 2008). The studies on the isolation of cellulase from beetles demonstrated that optimum pH for the highest activity of cellulase from the larval gut of Psacothea hilaris against CMC was 5.5 (Sugimura et al 2003). The results showed that CaCl 2 and MgCl 2 increased significantly endo-β-1,4-glucanase activity in R. ferrugineus.…”
Section: +mentioning
confidence: 99%
“…Cellulolytic activities have been detected in the gut of beetle larvae, thus, the gut is considered to be a site for lignocellulose digestion (Watanabe and Tokuda, 2001). The expression of endogenous cellulases has been confirmed in the gut of mustard beetles, Phaedon cochlearine (Chrysomelidae; Sugimura et al, 2003). Thus, studies describing the microbiota of S. levis larvae may contribute to find novel cellulose-degrading genes within the gut of insect.…”
Section: Introductionmentioning
confidence: 99%
“…There are genes that show higher levels of expression in certain tissues than in others or in specific stages of the beetle life cycle, so that studies focused on these genes benefit from a tissue or stage specific approach. This is the case of many studies interested in the characterisation of digestive enzymes, which use gut tissue as starting point (Girard & Jouanin, 1999a,b;Pedra et al, 2003;Sugimura et al, 2003;Zhu-Salzman et al, 2003;Bown et al, 2004;Gruden et al, 2004), or those centred in metabolic enzymes, focusing on the insect fat body, an organ involved in many homeostatic mechanisms and active centre of metabolic activity, where food reserves are stored in the insect and the maintenance of the balance between resources and requirements takes place (Smith et al, 1994;Vermunt et al, 1997Vermunt et al, , 1998Saito et al, 2004). In the case of genes specific of life cycle stages, those involved in the diapause or dormancy are a good example (Yocum, 2001(Yocum, , 2003.…”
Section: Genomic Pools Libraries and Cdna Sequencingmentioning
confidence: 99%